2012
DOI: 10.1590/s0104-11692012000500023
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal suction in intubated critically ill adult patients undergoing mechanical ventilation: a systematic review

Abstract: although the evidence obtained is relevant to the practice of endotracheal aspiration, the risks of bias found in the studies selected compromise the evidence's reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 23 publications
2
35
0
9
Order By: Relevance
“…This can be accepted as standard ES technique including: short time for MV disconnection and providing hyperoxygenation to avoid occurrence of hypoxemia as hypoxemia can result in hemodynamic instability. This result is in line with other studies (32,33) which showed that there was no statistical significant difference in BP after ES with or without saline. Preusser et al (34) found through studying patients with coronary artery bypass grafting operation that oxygenation before ES resulted in low fluctuations in MAP readings.…”
Section: Discussionsupporting
confidence: 93%
“…This can be accepted as standard ES technique including: short time for MV disconnection and providing hyperoxygenation to avoid occurrence of hypoxemia as hypoxemia can result in hemodynamic instability. This result is in line with other studies (32,33) which showed that there was no statistical significant difference in BP after ES with or without saline. Preusser et al (34) found through studying patients with coronary artery bypass grafting operation that oxygenation before ES resulted in low fluctuations in MAP readings.…”
Section: Discussionsupporting
confidence: 93%
“…(12,20,21) Even though the aspiration of tracheobronchial secretions can be a necessary procedure, it can be harmful to tracheal mucosa. (7) Studies about patient safety involving laryngotracheal injury are still incipient. (22) To minimize the occurrence of such lesions generated by the intubation process, healthcare teams must adopt preventive measures, such as rigorous and constant monitoring of intracuff pressure, adequate patient position and immobilization, adequate tube size, and carrying out tracheal aspiration.…”
Section: Discussionmentioning
confidence: 99%
“…Handling accidental extubation or self-extubation, and all other actions that result from nursing care of patients with artificial airways must be conducted so as to mitigate any injury due to mechanical ventilation and the maintenance of artificial airways. (6)(7)(8) The knowledge of clinical signs that suggest laryngotracheal injury, in addition to factors associated by the nursing team, is of crucial importance when planning safe intubated patient care. Thus, the objective of the present study was to describe the clinical signs of laryngotracheal mucosa injury and associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it recommends that minimally invasive suctioning be preferred, only when necessary. 18 Identifying the need for suctioning is a complex issue and requires knowledge and training of professionals inserted in clinical practice. Suctioning secretions is considered necessary when the patient presents cough, increased work of breathing, arterial desaturation and/or bradycardia, presence of audible or visible secretion, course breathing sounds during auscultation, or not enough lung volume after respiratory physical therapy to eliminate mobilized secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Suctioning secretions is considered necessary when the patient presents cough, increased work of breathing, arterial desaturation and/or bradycardia, presence of audible or visible secretion, course breathing sounds during auscultation, or not enough lung volume after respiratory physical therapy to eliminate mobilized secretions. [16][17][18] Verifying endotracheal cuff pressure is also a crucial practice for preventing VAP. The goal of this measure is to guarantee adequate seal of tracheal tube in order to prevent mirosuction of subglottic secretions and guarantee adequate ventilation.…”
Section: Discussionmentioning
confidence: 99%